Christianizing the Social Order: A Three-Dimensional Task - Hutchinson, Roger (Toronto journal of theology, 1996)
It is not as common today as it was in the 1930s to talk about Christianizing the social order. In our post-Christendom, pluralistic society such language has a triumphalist, imperialistic ring to it. The World Council of Churches' quest for justice, peace and the integrity of creation is now preferred as a vision for our day-the new language analogous to Christianizing the social order. My aim in this article is to reflect upon the assumptions about church and society and about the mission of the church embedded in Christianizing the social order image, especially as that understanding of Christianity was articulated in the 1934 report of the Commission on Christianizing the• Social Order. My main point will be that for the founding generation of the United Church Christianizing the social order was a threefold task involving the transformation of persons, social structures and culture.